Failure Analysis of Glulam Lumber Beam Made from Meranti Lumber Pieces (Shorea SP) - Murtopo, Ali; Jannah, Ria Miftakhul; Sabilla, Sabilla; Tsaniyah, Labibah (Semarang State University, 2020)
The development of glue-laminated (glulam) lumber beam gives many good results. Meranti (Shorea SP) is one of the construction lumber that can be used as glulam to optimize its use. The limitation of the glulam lumber beam is the limited length of the lumber, so it must be joined to get a certain length. The lumber available in the market on average has a limited size and cross-sectional length. The larger the cross-sectional size and length of the lumber make the higher the price. Used lumber and residual lumber also have many weaknesses, such as the length of suitable lumber is too short, lumber defects, and lumber damages. Further research needs to be done to optimize the use of new, used, and residual meranti lumber through the use of lumber pieces as a glulam lumber beam maker. Standard specimen and test based on ASTM D-198. Glulam lumber beam is made from pieces of meranti lumber planks of certain length which are arranged into lamina beam with the size of 5.5x9.5x150 cm3. Variations in the length of the pieces of meranti lumber planks for making glulam lumber beam, among others, 40 cm, 50 cm, 60 cm, 50 cm with full length lowest layer and 150 cm (full length). The adhesive used is polyurethane glue. The span between supports is 130 cm. The beam is tested for center point loading. The analysis results show that the joints on the outermost layer that receive tensile stress of the glulam lumber beam can cause weakening in the beam because the tensile strength of the adhesive is weaker than the tensile strength of lumber. Failure at the tensile joint of the outer layer of the beam can trigger a shear failure mode. Design of joints should not be placed on layers that are subject to tensile stresses so as not to trigger shear failure modes so that the strength of the glulam lumber beam can be optimal.